Communication on Progress: PRME Report 2008 - Ansgar Häfner; Norbert Jost; Karl-Heinz Rau; Roland Scherr; Christa Wehner; Hanno Beck (Hochschule Pforzheim, 2011)
Pforzheim University was one of the first 100 participants to sign the PRME initiative in March 2008. When we first learned about PRME we were immediately convinced that it was worthwhile joining it. It perfectly reflects our tradition and our mission statement. In the mission statements of our university and of the Business School we address our responsibility to society and we emphasize that our graduates should be able to contribute to corporate responsibility. Management education at Pforzheim University is mainly concentrated in the Business School. At the Engineering School the Business Administration and Engineering program is focused on Engineering as well as on Management. Furthermore, some of the graduates from the Design School and from the Mechanical and Electrical Engineering programs at the Engineering School also find themselves in management positions and hence aspects of responsible management are also relevant for their curricula. (...)
urn:nbn:de:bsz:951-opus-433
Keywords: B4; G3; 650; Corporate Social Responsibility; Betriebswirtschaftsstudium; Führungskräfteentwicklung; Corporate Social Responsibility